Stomatal Responses in Rainfed Lowland Rice to Partial Soil Drying; Comparison of Two Lines - Joel Dlc Siopongco; Kazumi Sekiya; Akira Yamauchi; James Egdane; Abdelbagi Ismail; Len Wade (Plant Production Science, 2009)
Previously, we demonstrated that root tips in drying soil communicate with shoots for stomatal closure in rainfed lowland rice, despite further water being available at depth. This study examines variation between two lines in root signals.Rice lines CT9993 and IR62266 were grown in the field, and in the greenhouse with the split-root root-sever wax-layer system, to investigate their responses to mild and severe water deficit by monitoring stomatal conductance (gs), leaf water potential and leaf ABA concentration. In the greenhouse, root systems were divided, withholdingwater from one portion, and in some cases, severing the droughted portion of roots to remove the signal. Wax layers differing in strength were placed at hardpan depth. Roots of CT9993 were better able to penetrate the wax layers. IR62266 exhibited stronger responses than CT9993, with IR62266’s stomatal conductance dropping sharply under water deficit, and recovering at slower rates but less completely, when roots subjected to drying soil were severed. The greater stomatal response in IR62266 was associated with a higher leaf ABA concentration during early water deficit, which in turn was associated with its greater number of roots in drying soil. In the field, a second reduction in gs wasobserved under severe water deficit, with stronger signals in IR62266 associated with more conservative water use as soil drying intensified. To better exploit subsoil water in mild or transient water deficit, selection for reduced root signals might be warranted.